THE INFLUENCE OF TEACHER PROFESSIONALITY ONTEACHER PERFORMANCE IN VOCATIONAL MADRASAHALIYAH (MAK) MADANI MANADO - Armin Abdullah (Penelitian dan Pengembangan Ilmu, 2024)
The education process in madrasas is always changing and developing in linewith the increasing competence and professionalism of teachers in the implementation ofeducation in madrasas. The same challenge is also faced by Vocational Madrasah Aliyah inintegrating Islamic educational values and nursing productive curriculum. So as astrategic step and a solution, the author tested the influence of teacher professionalism onteacher performance at Madrasah Aliyah Kejuruan Madani Manado. The method that theauthor uses in this study is a quantitative method. The research sample was madrasateachers, totaling 30 respondents in the research population. The research instrument useda questionnaire and hypothesis testing was carried out through a simple linear regressionanalysis test. The results of the study stated that there was a significant and positive effectIslamic Studies Journal (ISLAM)Vol xx(x) 202x : xx-xxof teacher professionalism on teacher performance at Madrasah Aliyah Kejuruan MadaniManado, thus Ha was accepted. The power of influence in the strong category is 0.687 andthe contribution given by teacher professionalism to teacher performance is 47.2%. Themore effective the improvement of teacher professionalism, the more the performance ofteachers at Madrasah Aliyah Kejuruan Madani Manado will increase.